2010
DOI: 10.4049/jimmunol.1000638
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Fibroblastoid Differentiation Mediated by Airway Smooth Muscle in Asthma

Abstract: Mast cell microlocalization to the airway smooth muscle (ASM) bundle is a key feature of asthma, but whether these mast cells have an altered phenotype is uncertain. In this paper, we report that in vivo, mast cells within the ASM bundle, in contrast to mast cells in the bronchial submucosa, commonly expressed fibroblast markers and the number of these cells was closely related to the degree of airway hyperresponsiveness. In vitro human lung mast cells and mast cell lines cultured with fibronectin or with prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
(49 reference statements)
3
24
0
Order By: Relevance
“…Stimulation with Th2 cytokine upregulated the mRNA expression of CXCL10 in ASMCs and the mRNA expression of CXCR3 in HMC-1 cells. Similarly, a recent study showed phenotype alteration of lung mast cells after infiltration into ASM bundles [33]. We also tested the expression of another CXCR3 ligand CCL11 in ASMCs but no significant difference was found after stimulation with IL-4 + IL-13 (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…Stimulation with Th2 cytokine upregulated the mRNA expression of CXCL10 in ASMCs and the mRNA expression of CXCR3 in HMC-1 cells. Similarly, a recent study showed phenotype alteration of lung mast cells after infiltration into ASM bundles [33]. We also tested the expression of another CXCR3 ligand CCL11 in ASMCs but no significant difference was found after stimulation with IL-4 + IL-13 (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…The number of mast cells has been shown to be elevated in ASM tissues of asthmatics compared to nonasthmatic subjects with or without other inflammatory disorders (31). The participation of mast cells in AHR has been suggested based on correlations observed between the percentage of mast cells recovered in the bronchoalveolar lavage fluid (BALF) (64) or interspersed in the ASM tissue (113) and the degree of airway responsiveness. Interestingly, the later correlation was even stronger when the mast cells with a fibroblastoid phenotype, which spontaneously produce more histamine, were counted (113).…”
Section: Inflammatory Cells and Moleculesmentioning
confidence: 99%
“…The participation of mast cells in AHR has been suggested based on correlations observed between the percentage of mast cells recovered in the bronchoalveolar lavage fluid (BALF) (64) or interspersed in the ASM tissue (113) and the degree of airway responsiveness. Interestingly, the later correlation was even stronger when the mast cells with a fibroblastoid phenotype, which spontaneously produce more histamine, were counted (113). It was also demonstrated using immunohistological sections of human airways that ASM cells that localized in vicinity of mast cells express higher levels of -smooth muscle actin (-SMA), suggesting a paracrine influence of mast cells that increases ASM contractility (255).…”
Section: Inflammatory Cells and Moleculesmentioning
confidence: 99%
“…While TGF 1 and connective tissue growth factor (CTGF) enhance collagen I and fibronectin production in normal and asthmatic ASM, differences in intrinsic signaling mechanisms likely alter ECM deposition in asthma (Burgess et al, 2003;Johnson et al, 2006). In asthma, mast cell localization to ASM bundles promotes mutual phenotypic changes that promote development of AHR (Kaur et al, 2010). For instance, in co-cultures IgE-independent mast cell release of -tryptase augments -SMA within ASM via autocrine actions of TGF .…”
Section: Asm and Disease Matrixmentioning
confidence: 99%